Investigating users' preferences for Low Emission Buses: Experiences from Europe's largest hydrogen bus fleet. (September 2019) - Loría, Luis Enrique; Watson, Verity; Kiso, Takahiko; Phimister, Euan
Highlights: We investigate bus users' preferences for emission reduction in bus travel. We conduct a Discrete Choice Experiment amongst Aberdeen bus users. We make use of a natural experiment – the Aberdeen Hydrogen Bus Project – to examine the role of direct experience in preferences. Bus users place a higher value in the reduction of local pollutants over greenhouse gas emissions. Increasing experience using a hydrogen bus has an effect on preferences for the comfort and bus emissions attributes.